High frequency hearing loss following treatment for nasopharyngeal carcinoma - Sumitsawan Y. (2014)
Objective: To evaluate the prevalence, severity and differences of high frequency hearing loss in nasopharyngeal carcinoma patients after curative treatment by radiotherapy alone and chemoradiation. Material and Method: Pure tone audiometry was done in nasopharyngeal carcinoma patients who came back to follow-up after curative treatment during the year 2003 and 2004. The patients were divided into three groups, the first group received radiation treatment only, the second group received radiation and cisplatin chemotherapy, and the third group received radiation and carboplatin chemotherapy. Results: Of 192 patients with a mean age 49.9 years, mean radiation dose 6,951.5 cGy, mean follow-up period 3 years and 9 months, 93.8% showed bilateral high frequency hearing loss. There were statistically significant differences in the high frequency hearing threshold between the second group versus the first and the third group. Conclusion: Clinicians should inform patients of the risk of hearing loss, particularly the treatment with cisplatin. Hearing test should be a routine test after treatment completion.